ANALISIS SEMIOTIKA AMANAT DALAM FILM “ASSALAMUALAIKUM BEIJING” KARYA ASMA NADIA - Rina Rosdiana; Risma Fitria; Rosi Rosi (IKIP Siliwangi, 2018)
The message the authors want to convey to the readers of the noble values that can be an example or role model. Submission of massages is based on the purpose set by the author at the time of darting the ceriate. The message delivered in a writing is not always written. An express mandate is a mandate described in a post. While the implied mandate is a mandate not explained in writing, but can be read through the storyline in writing. Assalamualaikum Beijing by Asmanadia which is interesting to see in terms of an interesting mandate and contains a mandate that we can quote like a bow and arrow. The methodology used in this study is semiotics analysis, hemis research used is kualitatif with descriptive research nature.